The loss of public sphere: outdoor advertising and commercialization of public spaces in Sleman, Yogyakarta, Indonesia - Rianto, Puji (Penerbit Universiti Kebangsaan Malaysia, 2020)
The commercialization of public spaces is one of the crucial issues in Yogyakarta Special Province, Indonesia. This study examines the loss of public spaces on Kaliurang and Affandi street, Sleman, Yogyakarta. Applying the case study as a research method, the data were collected through close observations to the advertisements, billboards, banners, posters, and other outdoor media along Jl. Kaliurang and Affandi street. During the data collection, the author has taken some photos in certain spots of these two locations. The study finds that the massive occupation of outdoor advertising in the public spaces along these two areas has not only causing visual trash but also causing the loss of the public sphere. It is caused by several factors. One of the most important factors is the weakness of local government regulations. Another factor is the spatial capitalization of the Yogyakarta Special Region and Sleman Regency in recent years as could be seen from the wide establishment of hotels, malls, supermarkets, and minimarkets in Yogyakarta. As a result, the public does not have enough space to express their voices and interests. Furthermore, the dominance of outdoor advertising has resulted in the dominance of commercial discourse in public spaces and has simultaneously marginalized or even eliminated public discourse. Public space has eventually transformed into commercial and has no longer become an important tool for democracy. Conversely, it has become an important tool for promoting consumer culture.